2020
DOI: 10.1002/smll.202003973
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mg2+ and Al3+ Substitutions on the Structural and Electrochemical Properties of NASICON‐NaxVMn0.75M0.25(PO4)3 (M = Mg and Al) Cathodes for Sodium‐Ion Batteries

Abstract: structure is made of so-called "lantern units" which consist of two VO 6 octahedra and three PO 4 tetrahedra. These lantern units are stacked along c-axis to make 3D framework, wherein sodium ions occupy two independent crystal sites (Na(1) and Na(2)). [8] It delivers reversible capacities closer to 110 mA h g −1 at an average intercalation voltage of 3.4 V versus Na + /Na 0 , resulting an energy density of ≈400 Wh kg −1. The corresponding electrochemical sodium (de)intercalation reaction proceeds through a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 33 publications
(56 reference statements)
0
47
0
Order By: Relevance
“…The increase of Na1 population would in turn weaken the electrostatic repulsion between two TMO 6 octahedra, finally resulting in the decrease in c parameter. [16,36] Thus, VMF-0.5 shows slightly larger c value due to its low Na1 occupancy, which is expected to provide a facile Na-ion diffusion by the expansion of the c-axis. Fouriertransform infrared spectroscopy (FTIR) data were recorded to reveal more structural information of as-prepared samples (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The increase of Na1 population would in turn weaken the electrostatic repulsion between two TMO 6 octahedra, finally resulting in the decrease in c parameter. [16,36] Thus, VMF-0.5 shows slightly larger c value due to its low Na1 occupancy, which is expected to provide a facile Na-ion diffusion by the expansion of the c-axis. Fouriertransform infrared spectroscopy (FTIR) data were recorded to reveal more structural information of as-prepared samples (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…However, as the Na + ions incorporated, the increased Na1 occupations would instead reduce the electrostatic repulsion between MO 6 (M = Fe, V) octahedra in c axis direction, resulting in the lowered c values. [29] In addition, the average bond lengths of Na2O for Na 3+x V 2-x Fe x (PO 4 ) 3 were also calculated (Figure S3), which is associated with their electrochemical performances. A long Na2O bond means the facilitated Na extraction/insertion from/into the cathode, usually representing better electrochemical properties.…”
Section: Materials Designmentioning
confidence: 99%
“…Ghosh et al developed a Mg-doped Na 4 VMn 0.75 Mg 0.25 (PO 4 ) 3 composite cathode, which shows an improved cycling stability. 14 Kim's group also incorporated Cu 2+ for substitution of Mn 2+ to obtain a Na 4 VMn 0.9 Cu 0. electrochemical performance. 15 More recently, our group demonstrated that lowering the Jahn−Teller effect of Mn 3+ on the electrochemical performance of cathodes by reducing the Mn concentration under the employment of Fe ions as dopants is effective.…”
mentioning
confidence: 99%